ANALISIS DEBIT PEMOMPAAN DI SUMP CENDANA SELATAN PT. BHUMI RANTAU ENERGI PROVINSI KALIMANTAN SELATAN - Simanjuntak, Eppi Marina; Indrajaya , Fahrul; Novalisae, Novalisae (Fakultas Teknik Universitas Palangka Raya, 2024)
PT Bhumi Rantau Energi is one of the mining companies engaged in coal with a surface mining method, which forms a basin on the surface so that it has the potential to cause water ingress into the mining pit area. The mining direction of PT Bhumi Rantau Energi is towards seam G precisely in the south sandalwood sump, for this reason it is necessary to maintain the water elevation in the sump so as not to overflow, reduce and drain the water in the sump because there will be coal mining activities in the south sandalwood sump area. For this reason, it is necessary to know the pumping discharge needed to cope with the water entering the south sandalwood sump. Measurement of pumping discharge is carried out by the discharge method, namely using an L-shaped measuring instrument at the pumping outlet so that the discharge of the DND 200-MHX pump is 397.90 m3 / hour with an efficiency of 76% while the MF 420-EXH pump is 493.69 m3 / hour with an efficiency of 70%. Based on the results of the pumping analysis, to maximize the pumping discharge, it is necessary to operate the pump simultaneously which aims to produce a maximum pumping discharge in dealing with water in the south sandal sump, and it is necessary to carry out pumping maintenance so that the resulting pumping discharge is greater.